KERAGAAN FINANSIAL KOPERASI PETERNAKAN BANDUNG SELATAN (KPBS) PANGALENGAN, JAWA BARAT - Bambang Sumantri; Nurhayatin Nufus (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2005)
Two main problems usually faced by corporation including cooperation are fund providing and allocation. KPBS as cooperation and as an economic unit also encounter these problems and has to operate efficiently to gain the profit in order to meet obligation and continuity. However, to attain these aims KPBS faces with fund financing problem and productivity of milk cows. The purpose of this research is to find out the value of financial rate ratios since 1993 – 2002, and compares the financial condition at the same period. The available data be analyzed with financial ratios in consist to Liquidity, Activity, Solvency, and Rent ability. This research show the value of KPBS’s financial performance 1993 during 2002 are: (a) Liquidity ratio, the highest value was 218,96% in 1997 and the lowest was 152,03% in 2002, this condition was still stated liquid because over to 100%; (b) Activity, 73,73 times in the supply period ratio in 2001 was highest then the other years, and the lowest was 4,85 times claim period in 1995 (c) Solvency, the highest value was 386,57% in capital ratio with permanent assets (solvable, because it’s over to 100%), and the lowest value in 1994 at the capital ratio with total assets, it was 36,64%; (d) Rent ability, 19,05% in 1993 was the highest value, and the lowest in 1995 was 0,6%. In case of milk productivity, the volume milk production decrease year by year and has an impact on KPBS financial performance which indicated by Ransum Concentrate (RC) application with protein under national RC standard, that is only 12% from 18% or 75% from 100%. With this condition KPBS should repair RC protein application, and maintaining production price. So that selling price still on breeders expectation.